Cervical cancer screening, treatment and prophylaxis in Brazil: Current and future perspectives for cervical cancer elimination - Corrêa, Flávia M.; Migowski, Arn; de Almeida, Liz M.; Soares, Marcelo A. (Frontiers in Medicine, 2022)
As a middle-income country, Brazil has one of the largest public health systems worldwide, which deals with free and universal access to health care. Regarding cervical cancer, the country possesses a large infrastructure for the screening of premalignant and malignant lesions, but yet based on old technology, having Papanicolaou as the major screening method, followed by colposcopy and treatment. Also, large disparities in access are present, which makes effectiveness of screening and treatment in different regions of the country highly unequal. In this review, we describe and evaluate the current screening, treatment and prophylactic (HPV vaccination) strategies to combat cervical cancer in Brazil, and discuss potential incorporation of more recent technologies in these areas in the country to pave its way towards cervical cancer elimination.